Wajah Baru Bina Iman Anak Katolik (Biak) Selama Masa Pandemi Covid-19 - Chrystian Loudry Malau; Antonius Denny Firmanto; Nanik Wijiyati Aluwesia (Jurnal Pelayanan Pastoral, 2021)
The presence of the Covid-19 pandemic has had a major impact on human life, especially the Church itself. For the Church itself, the perceived influence is that the Church has been led to a policy of changing its pastoral ministry, which is usually face-to-face, now using online or online media. The result of this policy is that the activities of the faithful become obstructed. One of the activities of the faithful that has been impacted by the emergence of the Covid-19 pandemic is Catholic Child Development (BIAK). Since the pandemic era, BIAK, which is usually done face-to-face, has now changed to BIAK online . This activity has been carried out by the St. Parish. The Virgin Mary from Mount Karmel, Malang. The changes that have occurred indicate that the Church has a listening attitude, especially during the Covid-19 pandemic. This situation brings a new face to BIAK, namely BIAK online which is increasingly modern.